Influence of Cusp inclination and type of retention on fracture load of implant-supported crowns - de Melo Rocha, Cibele Oliveira [UNESP]; Longhini, Diogo [UNESP]; de Paula Pereira, Rodrigo [UNESP]; Filho, João Neudenir Arioli [UNESP] (FapUNIFESP (SciELO), 2017)
There are few informations about the influence of cusp inclination on the fracture strength of implant-supported crowns. The study aimed to evaluate the influence of cusp inclination and retention type on fracture load in implant-supported metal-ceramic single crowns. Sixty crowns were made, classified as cemented and screw-retained with screw access hole (SAH) sealed or not. Standard (33°) and reduced (20°) cusp inclinations were tested for each group (n=10). To support crowns of a mandibular second molar, analogs of external hexagon implants 5.0 were used. The fracture load was measured in a universal testing machine EMIC DL2000 (10 kN load cell; 0.5 mm/min). Two-way ANOVA (retention and cusp inclination) followed by post hoc Tukey’s honest significant difference test was used for the statistical analyses (α=0.05). Crowns with reduced cusp inclination exhibited significantly higher fracture load (p<0.01) than crowns with standard cusp inclination. Cemented crowns showed significantly higher fracture load (p<0.01) than screw-retained crowns. The interaction among these factors was not significant (p>0.05) for the fracture load. The sealing of SAH did not influence the fracture load of screw-retained crowns (p>0.05). In conclusion, fracture load of implant-supported metal-ceramic crowns was influenced by retention and cusp inclination, and there was no influence of the sealing of SAH.
Keywords: Dental prosthesis; Implant-supported crowns; Material resistance